State of the Art Analysis: mapping the awarding certification landscape in Higher Education and Research - Giulia Nason; Maria Sangiuliano (Zenodo, 2020)
The State of the Art Analysis is the second public deliverable of the CASPER project (D3.3). It follows the“ Policy Framing Report ” (D3.1) and focuses on the description and analysis of the certification and awarding schemes identified in the EU 27 countries plus Australia, Iceland, Norway, United Kingdom, Switzerland, and the USA. Moreover, the State of the Art report provides an overview of the main policies and measures adopted at the national level to integrate gender equality in Research and Higher Education. The main objective of this deliverable is to provide a comprehensive overview of the certification and awarding landscape, providing information on the certification and awards’ methodologies, organisers and stakeholders. Additionally, it analyses the States national contexts to better situate the CASPER scenarios in the next steps of the project. Finally, it highlights the best and most widespread good practices at the international level, and it reflects on their potential uptake for a possible European-level certification on Gender Equality in Research and Higher Education. This project has received funding from the European Union's Horizon 2020 research and innovation programme under grant agreement No 872113. Version2: Deliverable revised and approved by EC